Village Development in Indonesia - Andhika Rafi Sunggoro (Indonesian Journal of Multidisciplinary Science, 2022)
The purpose of this article is to get to know villages and village development, the status of village progress in village funds, challenges and inhibiting factors for village development, as well as, what is the current condition of village development in Indonesia. The research material uses secondary data sourced from the Village Information System issued by the Ministry of Villages, Development of Disadvantaged Regions and Transmigration of the Republic of Indonesia in 2019-2021, and uses qualitative analysis methods. The results of the study show that the condition of villages in Indonesia today is mostly developing villages. There are quite a lot of villages that are very underdeveloped or underdeveloped, while villages with independent or developed status are still very few if you look at it in comparison with all villages in Indonesia.